A strategy of the new “green revolution” in wheat breeding: celebrating the jubilee of Lyudmila A. Bespalova, Full Member of the Russian Academy of Sciences - E. K. Khlestkina (Труды по прикладной ботанике, генетике и селекции)
On April 2, 2022, the national and international scientific communities who specialize in wheat breeding and agricultural producers in the wheat sector celebrated the birthday jubilee of Acad. Lyudmila A. Bespalova, a renowned breeder and head of the Department of Wheat and Triticale Breeding and Seed Production at the P.P. Lukyanenko National Grain Center.The main result achieved by L.A. Bespalova’s team is more than 170 cultivars of various wheat species and triticale, including over 100 bread wheat cultivars that supply about 10% of worldwide grain harvests of this staple crop, most important for the existence of mankind. The team succeeded in commercializing their competitive wheat cultivars with unique combinations of agronomic traits (grain quality, adaptability to abiotic and biotic stressors, short growing season, etc.) because they developed and implemented a new industrial breeding system, unmatched in the world. In its essence, the approach developed under the leadership of L. A. Bespalova at the P.P. Lukyanenko National Grain Center is a practically proven strategy of the new “green revolution” capable of ensuring the global food security.